Differences in glottic and supraglottic behavior and vocal fold structure in women with odynophonia and asymptomatic women - Fuentes, Christopher; Biermann, Christopher (Revista de Investigación en Logopedia, 2022)
The study of odynophonia has been scarcely addressed by the sciences related to vocal pathology and rehabilitation. The understanding of essential aspects for its therapeutics, such as glottic and supraglottic behavior, is still emerging. The aim of this study was to compare glottic and supraglottic behavior and vocal fold structure in women with odynophonia and asymptomatic women. We worked with 50 women with professional voices; whose average age was 25.78 ± 3.50 years old. Two groups were formed, G1 (asymptomatic women) and G2 (women with odynophonia). A videolaryngoscope with continuous lighting was used to examine supraglottic behavior and chordal structure, and an electroglottograph was used to analyze vocal fold behavior. In supraglottic behavior, 64% of G2 participants showed a greater severity than G1. The union between anteroposterior shortening and medial compression was the most frequent configuration in G2 and anteroposterior shortening alone was in G1. In 60% and 84% of G2 subjects, prominence of the vocal process and ventriculus spacious was observed along with a thinned vocal cord, respectively. Electroglottography revealed that the closed quotient was 0.50 ± 0.34 in G1, and 0.41 ± 0.31 (P < 0.05) in G2. In conclusion, in women with odynophonia, signs of chordal atrophy were observed, while in oscillation compensatory supraglottic compressions and anomalies related to chordal approximation or adduction were observed.